Innovative potential of Germany: the use of experience in Ukraine - Andriy Khimchenko; Oleksandra Popovych (Cхід, 2013)
In this article the current state of innovation policy in Germany and the use of its experience in Ukraine are considered. Statistic information on the sources of funding is presented in details, as well as the number of government programs that promote research and development activity. On the base of analyzed data, the direct of innovative development of Ukraine is proposed.